A fault-tolerant photovoltaic integrated shunt active power filter with a 27-level inverter - Kamel Saleh; Ameen Madi (Institute of Advanced Engineering and Science, 2021)
This paper introduces a fault-tolerant shunt active power filter (SAPF). The novility in of this work is that it poposes a solutions to increase the reliability of shunt active power filter to maintain its operation under a single-phase open-circuit fault in the SAPF. This will increase the reliability of the whole power system. The SAPF is composed of a 4-leg 27-level inverter based on asymmetric cascaded H-bridge topology. If an open-circuit fault is introduced to the operation of the SAPF, a special control technique will be implemented and the redundant leg of the SAPF will be activated. The fault-tolerant SAPF can do many tasks under healthy operating conditions and post and open circuit fault depending on the state of charge (SOC) of the batteries. It can mitigate harmonics in the power system, improve power factor in the system by injecting reactive power, and inject real power to the system. The proposed SAPF is tested and simulated in MATLAB/Simulink and the results have shown a significant improvement in total harmonics distortion (THD) of the source current from 13.9% to 3.9% under the normal operating condition and from 42% to 8.4% post and open circuit fault.